Do fiscal rules decrease public investment? Evidence from European panel data - Sebastiaan Wijsman; Christophe Crombez (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
This paper studies the effects of fiscal rules on public investment. Economists argue that fiscal rules decrease public investment, as it is easier for governments to lower public investment than current expenditures. This paper presents an empirical assessment of the relationship between fiscal rules and public investment using European panel data covering the 1997–2016 period. In contrast to previous work, we focus on national fiscal rules and use the European Commission's Fiscal Rules Strength Index to measure the constraints imposed on public finances. This index captures 230 national fiscal rules and reflects the annual strength of fiscal rules in each European Union member state. In line with our expectations, we find that fiscal rules decrease public investment. We run some additional models in which the results are mixed.
Keywords: E62; H54; 330; public investment; fiscal rules